Neutrophil/Lymphocyte Ratio (NLR) and Lymphocyte/CRP ratio (LCR) are Reliable Predictors of Adverse Outcomes in High-Altitude COVID-19 Patiens - Jimenez-Aguilar, Rosalinda (2023)
The neutrophil/lymphocyte ratio (NLR) and the lymphocyte/C-reactive protein ratio (LCR) are prognostic factors in inflammatory, cardiovascular, and oncological dis eases. With the emergence of the COVID-19 pandemic, it has been recently shown that NLR and LCR are also useful for the prognosis of disease severity in patients infected with the SARS-CoV-2 virus at sea level. However, there are no studies demon strating the reliability of NLR and LCR in high-altitude human populations (above 2,500 m). This is relevant because both the incidence and mortality from COVID-19 are decreased in high altitude. A possible explanation of this effect is a lower impact of this virus on the exaggerated inflammatory response induced by the viral infection. The aim of this study is to determine whether the NLR and LCR indices can be used as reliable predictive markers of COVID-19 severity in high-altitude permanent resident patients. Routine blood biochemistry and complete blood count were performed on 368 patients positive for the SARS-CoV-2 virus in Huaraz, Peru (3,050 m). Patients’ follow up was carried out until home discharge or fatal outcome. The results show that: 1) NLR values are higher in deceased patients admitted to the intensive care unit due to COVID-19; 2) NLR and LCR are reliable predictors of death in patients with COVID-19; and 3) NLR and LCR are reliable predictors of intensive care unit require ment in COVID-19 patients. We conclude that NLR and LCR are reliable biomarkers and prognostic factors of COVID-19 severity and can be used in high-altitude per manent resident patients.